Penerapan Model Cooperative Learning Tipe NHT Menggunakan Media Pebelajaran Rolling Ball Game terhadap Hasil Belajar Pada Kelas XI Madrasah Arifah Gowa - Jafar, Andi Ferawati (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
This study aims to determine the learning outcomes of students using the NHT type cooperative  learning  model  using  rolling  ball  game  learning  media  on  learning outcomes  in  class  XI  Madrasah  Arifah  Gowa.  The  research  method  used  is  quasi-experimental with Noneequivalent control group design. The sample of this research is class  XI.1  as  many  as  32  people  and  XI.2  as  many  as  27  people.  Data  collection  is done  by  using  a  test  of  learning  outcomes  in  the  form  of  multiple  choice  questions. The statistical methodused descriptive analysis, inferential analysis, homogeneity test and  hypothesis  testing.  Based  on  the  results  of  calculations  using  the  independent sample  t-2  test  using  IBM  SPSS  v.20  obtained  a  value  of  4.838  and  the  t  table  is sought  by  referring  to  the formula (α/2); (df) is equal to (0.05/2) ; (57). So that the value of the t table in the distribution of the t value of the statistical table is 2.002, thus the  t-count  value  is  4.838  >  t-table  2.002,  so  based  on  decision  making  through  the comparison ofthe t-value  with t-table, it can be  concluded that H0 is rejected and H1 is accepted,  which  means there are  differences in physics learning outcomes between the  control  and  experimental  classes  or  in  other  words  the  application  of  the  lecture model  with  the  NHT  type  cooperative  learning  model  using  the  rolling  ball  game learning  media  will  produce  different  physics  learning  outcomes.  The  implication  of this  research  is  that  it  is  expected  that  educators  can  apply  the  NHT  type  cooperative learning model using rolling ball game learning media as an alternative in the teaching learning process to improve student learning outcomes.